Development of a cognitive screening instrument for tribal elderly population of Himalayan region in northern India - Sunil Kumar Raina (Journal of Neurosciences in Rural Practice, 2013)
Introduction: Cognitive impairment, characteristic of dementia, is measured objectively by standard neuropsychological (cognitive) tests. Given the diversity of culture and language in India, it is difficult to use a single modified version of MMSE uniformly to Indian population. In this article, we report methods on the development of a cognitive screening instrument suitable for the tribal (Bharmour) elderly (60 years and above) population of Himachal Pradesh, India. Materials and Methods: We used a systematic, item‑by‑item, process for development of a modified version of MMSE suitable for elderly tribal population. Results: The modifications made in the English version of MMSE and the pretesting and pilot testing thereof resulted in the development of Bharmouri version of cognitive scale. Discussion: The study shows that effective modifications can be made to existing tests that require reading and writing; and that culturally sensitive modifications can be made to render the test meaningful and relevant, while still tapping the appropriate cognitive domains.